Impact of transactional leadership style on the performance of a project-based carpentry organisation in the Western - Tinise, Aphiwe (Cape Peninsula University of Technology, 2022)
Most studies on leadership management concentrate primarily on other leadership styles, with less emphasis placed on transactional leadership and employee performance, particularly in project-based organizations. The study identified gaps in the literature regarding the relationship between organizational success and personnel productivity in the carpentry industry. The study's goal was to contribute to the existing literature on transactional leadership and the effectiveness of transactional team members, both of which impact the success of a transactional leader. The study aimed to link transactional leadership and the performance of carpenters in a transactional-based organization with elements that influence carpentry performance. The methodology involved the use of quantitative methods in gathering data consisting of both open and closed-ended questions. Given the option to participate voluntarily and cancel at any time, to conduct the research, participant consent is required. This guaranteed that personal details, including names, identity numbers, and mobile numbers, were not to be shared with third parties. The poor employee performance of the project-based organization in the Western Cape was found to largely to be due to inappropriate planning, organizing, and project/task tracking, poor leadership/management, a lack of resources, a lack of training opportunities, and a lack of employee empowerment. Additionally, poor communication leads to production delays, and favouritism on the part of the employer has an impact on how well other employees perform. The study suggested steps that could help to enhance the performance of the carpentry industry, such as effective planning, clear job communication, as well as making sure that human resources and material procurement are in place and implementing more training programs. The study was significant as it highlights the connection between transactional leadership style and worker performance in a carpentry-based business. It, therefore, assists carpentry-based organizations in adopting leadership styles which are beneficial and contribute to the successful delivery of transactional objectives. It helps organizations identify the right leader at the right place. Moreover, it adds to the existing body of transactional management leadership in other sectors and industries by improving performance and productivity.
Thesis (MTech (Business Administration in Project Management))--Cape Peninsula University Of Technology, 2022
Keywords: Transactional Leadership Style; Carpentry -- Personnel management; Leadership; Carpentry -- Employees --Performance; Organizational effectiveness; Success in business; Labor productivity; Organizational behavior